Applications Of The Immune-Histochemical Technique For Diagnosis Of Helicobacter Pylori From Gastric Biopsy Samples (Journal of Pharmaceutical Negative Results, 2023)
Applications Of The Immune-Histochemical Technique For Diagnosis Of Helicobacter Pylori From Gastric Biopsy Samples